Surfing the World of Knowledge: Analytical Case Studies of Digital Liberties in the United States - Liu, Dr Yan Quan (Independently published, 2021)
This work compiles a database that provides analytical case studies of typical digital libraries as an enhancement for educating and learning to meet the needs of students, librarians, scholars, and those who are interested in this resource.
Keywords: dept.ils

Exploring library core competencies: A text mining study of american library association’s job advertisements from 2006 through 2017: - Yang, Qinghong; Shi, Zehong; Liu, Yan Quan (Social Science Computer Review, 2021)
Are core competency requirements for relevant positions in the library shifting? Applying natural language processing techniques to understand the current market demand for core competencies, this study explores job advertisements issued by the American Library Association (ALA) from 2006 to 2017. Research reveals that the job demand continues to rise at a rate of 13% (2006–2017) and that the requirements for work experience are substantially extended, diversity of job titles becomes prevalent, and rich service experience and continuous lifelong learning skills are becoming more and more predominant for librarians. This analytical investigation informs the emerging demands in the American job market debriefing the prioritization and reprioritization of the current core competency requirements for ALA librarians. © The Author(s) 2021.
Keywords: dept.ils; peer-reviewed

Bridging digital divides during COVID-19: Findings from the 2020-2021 connecticut state library digital inclusion survey - Real, Brian (Public Library Quarterly, 2021)
This article presents findings from the 2020–2021 Connecticut State Library Digital Inclusion Survey. The primary purpose of this study was to determine what actions public libraries in Connecticut are already taking to meet the digital inclusion needs of their communities and what information and assistance they need to better meet these goals. However, since this study was launched during the COVID-19 pandemic, the author customized numerous questions to focus on how public libraries have adjusted their operations when patrons have had limited access to library buildings. Responses from public library representatives throughout the state show that libraries have used tactics such as delivering previously in-person public programs through video conferencing formats and shifting portions of their physical materials budget to support digital items. © 2021 The Author(s). Published with license by Taylor & Francis Group, LLC.
Keywords: dept.ils; peer-reviewed

Public library events: Who, what, where, when, and why? - Kukiolczynski, Katie Teresa; Liu, Yan Quan (Public Library Quarterly, 2021)
An explorative survey pertaining to organization and execution of programs and events offered in public libraries across Connecticut revealed that library programs have been steadily increasing in recent years, with most libraries providing one hundred or more programs a year. The types of programs that are most popular vary throughout the library’s open hours. Children’s programming appears to be more popular during the day while adult programming is more popular in the evening. Program popularity is based on grouping and continuous support from external partners. While this study confirmed that both library space and library staff sizes are adequate for programming, a further investigation would assert that this is the case within nationwide library programming.
Keywords: Connecticut; Public libraries; dept.ils; library events; library programs; peer-reviewed